2022
DOI: 10.1007/s00484-022-02382-3
|View full text |Cite
|
Sign up to set email alerts
|

Space weather phenomena on heart rate: a study in the Greek region

Abstract: Many scientific investigations have focused on how space weather phenomena, taking place in the vicinity of the Earth, may influence different aspects of life on Earth and presumably human health itself. From 2005, the National and Kapodistrian University of Athens has established an important position in the field of these investigations by collaborating with various scientists and Institutes, both international and domestic, in different heliobiological projects. In this work, the Cosmic Ray Group of the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Geomagnetic disturbances and variations in cosmic ray activity can have an impact on the human physiological state and affect the variability of HR. The results obtained in this study are in accordance with results from similar studies [18,19,25], where it was concluded that intense geomagnetic activity and strong CRI decreases are connected to an HR increase. The novelty of this study is that HR data were analyzed during different phases of the solar cycle 24.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Geomagnetic disturbances and variations in cosmic ray activity can have an impact on the human physiological state and affect the variability of HR. The results obtained in this study are in accordance with results from similar studies [18,19,25], where it was concluded that intense geomagnetic activity and strong CRI decreases are connected to an HR increase. The novelty of this study is that HR data were analyzed during different phases of the solar cycle 24.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…For 132 individuals (10%), data concerning their gender were not obtained. The Holter electrocardiogram method was used for obtaining the hourly mean HR of the group of individuals (for more details on the Holter method see [25]).…”
Section: Medical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…usually increase for high levels of geophysical activity [49]. In fact, higher HR values are observed for the highest GMA levels, i.e., levels III and IV of the Dst index classification, while small or even no variations are recorded for the lowest GMA levels, i.e., levels I0, I and II of the Dst index classification [42,47,50]. This behavior is observed in Figure 2 for women, where indeed the maximum HR value is registered for Dst index level IV, but not for men.…”
Section: Resultsmentioning
confidence: 94%
“…For the time period from April 2011 to January 2018 (i.e., solar cycle 24), 534 women with a mean HR of 72.5 ± 0.8 bpm and 687 men with a mean HR of 70.3 ± 0.6 bpm were examined. Daily HR data were obtained with a Holter electrocardiogram [42].…”
Section: Medical Datamentioning
confidence: 99%